Competitive repopulation of an empty microglial niche yields functionally distinct subsets of microglia-like cells - Harald Lund; Melanie Pieber; Roham Parsa; Jinming Han; David Grommisch; Ewoud Ewing; Lara Kular; Maria Needhamsen; Alexander Espinosa; Emma Nilsson; Anna K. Överby; Oleg Butovsky; et al. (Nature Communications, 2018)
Brain microglial cells can be replenished by blood-derived monocytes, but many aspects of this repopulation remain unclear. Here the authors show that the brain microglial niche can be replaced both by proliferating, residential microglia as well as differentiated Ly6Chi monocytes, with the latter having overlapping but distinct characteristics.